The Evolution of Nuclear Strategy - Freedman, Lawrence. author. aut Link
XVIII, 786 p.
Keywords: “The Evolution of Nuclear Strategy quickly established itself as a classic when it first appeared in 1981. This edition makes it even better, incorporating as it does new material about the Cold War and up-dating to include subsequent developments. Filled with insights and penetrating analysis, this volume is truly indispensable.” Robert Jervis, Author of How Statesmen Think "Freedman and Michaels have written a thorough and thought-provoking guide to nuclear strategy. The authors analyze the causes of both wise and unwise strategic decisions in the past and thereby shine a bright light on dilemmas we face in our common nuclear future." Scott Sagan, Stanford University, USA “With its comprehensive coverage, clear and direct language, and judicious summaries of a vast literature, this new and wholly revised edition of The Evolution of Nuclear Strategy will be essential reading for any student of nuclear history, strategic studies, or contemporary international relations.” Matthew Jones, London School of Economics and Political Science, UK First published in 1981, Lawrence Freedman's The Evolution of Nuclear Strategy was immediately acclaimed as the standard work on the history of attempts to cope militarily and politically with the terrible destructive power of nuclear weapons. It has now been completely rewritten, drawing on a wide range of new research, and updated to take account of the period following the end of the cold war, and covering all nuclear powers. Lawrence Freedman is Emeritus Professor of War Studies at King’s College London, UK. He was appointed Official Historian of the Falklands Campaign in 1997 and was a member of the official inquiry into Britain and the 2003 Iraq War. His most recent books include Strategy: A History (2015) and The Future of War: A History (2017). Jeffrey Michaels is Senior Lecturer in Defence Studies at King's College London, UK.